Annie B - Ignacio ([Pasig City] Viva Films Production, 2004)
Annie who comes from a poor family is the epitome of an active and lively teenager. Fernando Gonzaga is the owner of an advertising agency.
VCD
Story and screenplay by Rj Nuevas ; produced by Vicente G. Del Rosario III, Veronique Del Rosario Corpuz, executive producer Vic Del Rosario Jr., directed by Louie Lagdameo Ignacio.
Jolina Magdangal, Dingdong Dantes, Jordan Herrera.
Keywords: Feature films; Drama; Comedy